Metabolic biomarkers of response to the AKT inhibitor MK-2206 in pre-clinical models of human colorectal and prostate carcinoma. Issue 9 (30th October 2018) - Al-Saffar, Nada; Troy, Helen; Wong Te Fong, Anne-Christine; Paravati, Roberta; Jackson, L.; Gowan, Sharon; Boult, Jessica; Robinson, Simon; Eccles, Suzanne; Yap, Timothy; Leach, Martin; Chung, Yuen-Li
Abstract Background AKT is commonly overexpressed in tumours and plays an important role in the metabolic reprogramming of cancer. We have used magnetic resonance spectroscopy (MRS) to assess whether inhibition of AKT signalling would result in metabolic changes that could potentially be used as biomarkers to monitor response to AKT inhibition. Methods Cellular and metabolic effects of the allosteric AKT inhibitor MK-2206 were investigated in HT29 colon and PC3 prostate cancer cells and xenografts using flow cytometry, immunoblotting, immunohistology and MRS. Results In vitro treatment with MK-2206 inhibited AKT signalling and resulted in time-dependent alterations in glucose, glutamine and phospholipid metabolism. In vivo, MK-2206 resulted in inhibition of AKT signalling and tumour growth compared with vehicle-treated controls. In vivo MRS analysis of HT29 subcutaneous xenografts showed similar metabolic changes to those seen in vitro including decreases in the tCho/water ratio, tumour bioenergetic metabolites and changes in glutamine and glutathione metabolism. Similar phosphocholine changes compared to in vitro were confirmed in the clinically relevant orthotopic PC3 model. Conclusion This MRS study suggests that choline metabolites detected in response to AKT inhibition are time and microenvironment-dependent, and may have potential as non-invasive biomarkers for monitoring response to AKT inhibitors in selected cancer types.